Extemporaneous dermatological compounding in hospital pharmacies, Northwest Ethiopia - Dagnew, Ephrem Mebratu; Sendekie, Ashenafi Kibret; Tsega, Wondale; Mekonnen, Biset Asrade; Getachew, Melese (Frontiers in Public Health, 2025)
BackgroundDermatological problems are among the leading causes of hospital visits in Ethiopia. Extemporaneous compounded products are currently used by many patients with different disorders. The aim of the study was to evaluate the most commonly prescribed extemporaneously compounded products compounding practice and applicability of compounding guidelines at five randomly selected hospitals in Northwest Ethiopia.MethodsA hospital-based multicenter descriptive cross-sectional study was conducted by retrospectively analyzing prescription records for dermatological compounding from January to April 2023. A total of 423 prescriptions from hospital pharmacies were systematically selected. Data related to skin condition patterns, product selection, and dosage form types were extracted using a semi-structured data extraction tool and analyzed using SPSS version 25.0 at a significance level of 5%.ResultsA total of 423 prescriptions containing dermatological products for compounding were analyzed. Most patients were female (82.1%) and aged 30–64 years (46.3%). Melasma (82.9%), acne vulgaris (68.6%), acute dermatitis (63.27%), and Rosacea (61.54%) were the four top dermatological diseases for which compounding preparations were prescribed. More than half of the prescriptions (56.26%) contained a combination of two drugs. Most compounded dosage form was semisolid preparations (95.98%), while the remaining 17 (4.02%) were liquids. Salicylic acid (35.39%) was the most frequently prescribed active ingredient, followed by Clobetasone (13.03%) and Betamethasone (10.01%). Vaseline (47.62%) and Nivea cream (44.3%) were the most commonly used excipients for compound preparations. Hydroquinone (4%) with Nivea cream (30gm) (17.0%), followed by salicylic acid (5%) + Betamethasone (75 g) + Vaseline (20 g) (10.6%) were the most commonly prescribed dermatological formulations.ConclusionDermatological disease is more prevalent in the study area. and extemporaneous compounding is a common element of pharmaceutical care. Extemporaneous and topical semisolid preparations containing two or more active ingredients are the most widely compounded and prescribed products. This study suggests the application of good manufacturing practices and componding guidelines for extemporaneous compounding of dermatological formulations to ensure efficacy, quality, and safety.